Diseño de la estrategia de calidad de datos administrativos de prestadores de servicios en el sector de las tic y guía de aplicación a sectores públicos similares (2020)
Strategy for the quality of the administrative data of service providers in the ICT sector, through data knowledge, the generation of the guide and the design of MDM, in order to establish successful contact and generate consolidated information for decision-making